Extrinsic Motivation in Farming on Earthy Stone Land in the Binongko Island Wakatobi Regency South East Sulawesi - Hidrawati Hidrawati; Usman Rianse; R. Marsuki Iswandi; Nur Arafah (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
Coastal areas and small island communities in the Wakatobi archipelago carry out traditional agriculture. Farming is held with a rainfed system on dry land and a dry climate. This system theoretically has non-optimal productivity. Even so, farmers still farm because extrinsic motivation influences how they manage farming land. The productivity of their farms is relatively able to meet the needs of farmers. This study aims to determine extrinsically motivations attached to the traditional agricultural systems of the Binongko community in the Wakatobi Islands. The research lasted eight months, from June 2019 to February 2020. The research data was collected with the triangulation method by observation, interviews, and literature study. The research informants were determined purposively with a chain information collection system. The data were analysed qualitatively using a phenomenological approach. Based on the results of this study, it is known that the Binongko Island community has an extrinsic motivation attached to traditional farming systems, namely, to obtain agricultural products economically, socially, and ecologically. In addition, farmers are also extrinsically motivated by the support from the government. These local wisdom techniques are implemented starting from land preparation and clearing, planting, maintenance, harvesting and post-harvesting.